Inhibitory role of the KEAP1-NRF2 pathway in TGFβ1-stimulated renal epithelial transition to fibroblastic cells: a modulatory effect on SMAD signaling. - In-Geun Ryoo; Hunjoo Ha; Mi-Kyoung Kwak (PLoS ONE)
Transforming growth factor β1 (TGFβ1) is a potent stimulator of epithelial-to-mesenchymal transition (EMT) and has been associated with chronic kidney diseases by activating profibrotic gene expression. In this study, we investigated the role of the KEAP1-NRF2 pathway, which is a master regulator of the cellular antioxidant system, in TGFβ1-stimulated EMT gene changes using human renal tubular epithelial HK2. Treatment with TGFβ1 enhanced the levels of reactive oxygen species (ROS) and TGFβ1-stimulated EMT gene changes, including an increase in profibrotic fibronectin-1 and collagen 1A1, were diminished by the antioxidant N-acetylcysteine. In HK2, TGFβ1 suppressed NRF2 activity and thereby reduced the expression of GSH synthesizing enzyme through the elevation of ATF3 level. Therefore, the activation of NRF2 signaling with sulforaphane effectively attenuated the TGFβ1-stimulated increase in fibronectin-1 and collagen 1A1. Conversely, the TGFβ1-EMT gene changes were further enhanced by NRF2 knockdown compared to the control cells. The relationship of NRF2 signaling and TGFβ1-EMT changes was further confirmed in a stable KEAP1-knockdown HK2, which is a model of pure activation of NRF2. The TGFβ1-mediated increase of collagen 1A1 and fibronectin-1 in KEAP1 knockdown HK2 was suppressed. In particular, TGFβ1-SMAD signaling was modulated in KEAP1 knockdown HK2: the TGFβ1-stimulated SMAD2/3 phosphorylation and SMAD transcriptional activity were repressed. Additionally, the protein level of SMAD7, an inhibitor of SMAD signaling, was elevated and the level of SMURF1, an E3 ubiquitin ligase for SMAD7 protein, was diminished in KEAP1 knockdown HK2. Finally, the inhibition of SMAD7 expression in KEAP1 knockdown HK2 restored TGFβ1 response, indicating that SMURF1-SMAD7 may be a molecular signaling linking the NRF2-GSH pathway to TGFβ1-EMT changes. Collectively, these results indicate that the KEAP1-NRF2 antioxidant system can be an effective modulator of TGFβ1-stimulated renal epithelial transition to fibroblastic cells through the SMUR1-SMAD7 signaling, and further implies the beneficial role of NRF2 in chronic renal diseases.